Interaction of Bacillus spp. and Salmonella enterica Serovar Typhimurium in immune/inflammatory signaling from swine intestinal epithelial cells - Aperce, Celine (Kansas State University, 2008)
Previous research evaluated a laboratory strain of Bacillus licheniformis (BL) in a model swine epithelium and found it exerted anti-inflammatory effects on Salmonella enterica serovar Typhimurium (S)-induced secretion of interleukin-8 (IL-8). The current investigation evaluated the anti-inflammatory actions of Bacillus bacteria available commercially as feed additives for the swine industry. Three isolates were obtained from the product, two Bacillus subtilis (BS1 and BS3) and one Bacillus licheniformis (BL2). Swine jejunal epithelial IPEC-J2 cells were seeded into wells on permeable membrane supports and allowed to form confluent monolayers. Treatments included apical pretreatment with BL, BS1, BL2, or BS3 for 17 h without S, and the same Bacillus treatments but with 10[superscript]8 CFU S added in the final 1 h of Bacillus incubation. Two additional treatments included negative control wells receiving no bacteria (C) and positive control wells receiving only S. Following bacterial incubation, wells were washed and fresh media containing gentamicin was added. Cells were incubated for an additional 5 h, after which apical and basolateral media were recovered for quantitation of IL-8 and bacitracin. In addition, inserts with epithelial cells that had received S were lysed and lysates cultured to determine treatment effects on S invasion. Exposure to S alone provoked an increase in IL-8 secretion from IPEC-J2 cells compared to C wells (P < 0.001 for both the apical and basolateral directions). Pre-treatment with each Bacillus isolate followed by challenge with S reduced S-induced IL-8 secretion in both apical and basolateral compartments compared to the wells receiving only S (P < 0.001; except for BS3 apical, P < 0.01). Secretion of bacitracin could only be detected in BL2 and BL2+S. Fewer S colonies could be cultured from lysates of BL2+S than S, BS1+S, and BS3+S treatments (P < 0.001). Results suggest that Bacillus subtilis and Bacillus licheniformis have the ability to intervene in secretion of the neutrophil chemoattractant IL-8 from swine intestinal epithelial cells. This effect on chemokine secretion by gastrointestinal epithelial cells in vitro could not be explained solely by production of bacitracin or reduced invasion of epithelial cells by S.
Keywords: Bacillus; Salmonella; Swine; Biology, Animal Physiology (0433)